Recent Advances in Inverse Scattering, Schur Analysis and Stochastic Processes: A Collection of Papers Dedicated to Lev Sakhnovich - Alpay, Daniel (Springer, 2015)
The volume is dedicated to Lev Sakhnovich, who made fundamental contributions in operator theory and related topics. Besides bibliographic material, it includes a number of selected papers related to Lev Sakhnovich's research interests. The papers are related to operator identities, moment problems, random matrices and linear stochastic systems.